17 Cardiomyocytes Influence Fibroblast Proliferation and α-Smooth Muscle Actin Expression via the Secretion of Paracrine Mediators. (19th January 2014) - Kane, C; Cartledge, J; Dias, P; Camelliti, P; Yacoub, M; Terracciano, C
Abstract : Introduction: Cardiac fibroblasts are known to modulate cardiomyocyte structure and function through soluble mediators. While less studied, the ability of cardiomyocytes to influence fibroblast properties, such as proliferation and activation, is likely to be of equal importance, as myocytes are known to produce a number of soluble factors to which fibroblasts are sensitive. Further, whether disease alters this myocyte-fibroblast cross talk is an important question to address. Methods: Conditioned medium was obtained from culturing isolated rat ventricular myocytes from control or 16 weeks post-myocardial infarction rats (n = 3). Adult rat ventricular fibroblasts were treated with myocyte conditioned or control medium for 48 hrs. Proliferation and cytotoxicity was assessed by MTS and LDH assays and α-smooth muscle actin (SMA) expression by western blotting. Results: There was a 20% increase in fibroblast number in both the control and MI groups compared to baseline after 48 h (p < 0.001) of culture. There was a tenfold increase in cell death in control compared to MI (p < 0.001), but neither was significant compared to baseline. Fibroblast α-SMA levels were reduced in both control and MI groups to 50% of baseline (p < 0.01). Conclusion: Cardiomyocytes produce paracrine factors that modulate fibroblast proliferation, α-SMA expression and cytotoxicity. These effects, combined with the known modulation of myocyte activity by soluble mediators secreted by fibroblasts, highlights the complexity of this form of cell interaction. Differential effects produced by control and post-MI myocytes may suggest a role for myocyte modulation of fibroblast function in disease.